THE BELOMORIAN ECLOGITE PROVINCE (EASTERN FENNOSCANDIAN SHIELD, RUSSIA): MESO-NEOARCHEAN OR LATE PALEOPROTEROZOIC? - M. V. Mints; K. A. Dokukina; М. В. Минц; К. А. Докукина (Institute of the Earth's crust of the Russian Academy of Sciences, Siberian Branch, 2020)
A critical discussion of competing models of the geodynamic nature (oceanic or continental subduction) and age (Meso-Neoarchean or Late Paleoproterozoic) of the eclogite facies metamorphism in the Belomorian eclogite province (BEP) is based on the systematic analysis of the sum of previously known and newly obtained data characterizing the geological structure of the Salma eclogite association and features of zircons from eclogites, including the isotopegeochronological and geochemical characteristics, composition and distribution of mineral inclusions. Regular changes in the REE trends and crystallization-recrystallization temperature of porous zircons in eclogite-metagabbro illustrate the sequence of magmatic and metamorphic events in the Meso-Neoarchean and Paleoproterozoic. The susceptibility to recrystallization of zircons is due to partial metamictness and porous structure. The earliest (~2.9 Ga) zircon zones retain mag-matic-type REE trends. The microinclusions of the prenite-pumpelliite and greenschist facies minerals and the increase in the LREE and MREE concentrations indicate hydrothermal metamorphism in the spreading ridge and on the ocean floor at 2.9–2.82 Ga. Prenite, pumpelliite, albite, actinolite, chlorite, diaspore and saponite also form inclusions in the eclogitic garnet. An increase of LREE and MREE, the disappearance of the Ce positive anomaly, a change from negative to positive Eu anomaly at 2.82–2.78 Ga indicate that plagioclase was removed during the formation of the ‘garnet + omphacite’ eclogite association and the replacement of sphene with rutile. The eclogite facies metamorphism linked with subduction of the oceanic crust is also indicated by the microinclusions of garnet and rutile in zircon. The crystallization temperature in 700–900 °C range of the round-oval zircons from eclogites-metagabbronorites records the Neoarchean granulite facies metamorphism at 2.77–2.70 Ga, the negative Eu anomalies in the cores and rims of zircons indicate the participation of plagioclase in the ...